Mean number of the customers served during a busy period in the M|G|∞ queueing system - Ferreira, M. A. M. (Revista de Estatística, 2001)
We deduce an exact expression that gives the mean number of the customers served during a busy period in the M|M|∞ queueing system and conjecture an upper bound of this quantity for other M|G|∞ systems, with service times not exponential, based on the results of a Markov Renewal Process.